2007
DOI: 10.1590/s1678-77572007000600007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between inverted and unprocessed digitized radiographic imaging in periodontal bone loss measurements

Abstract: The advances in digital imaging technology in dentistry have provided an alternative to film-based radiography and have given new options to detect periodontal bone loss. The purpose of this study was to compare inverted and unprocessed digitized radiographic imaging in periodontal bone loss measurements. Thirty-five film-based periapical radiographs of patients suffering from moderate to advanced untreated periodontal bone loss associated to lower premolar and molars was selected from the department files, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
14
0
2
Order By: Relevance
“…[1] Periodontal disease leads to attachment loss, alveolar bone destruction, and subsequently loosening of teeth. The teeth more commonly involved are the molars.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Periodontal disease leads to attachment loss, alveolar bone destruction, and subsequently loosening of teeth. The teeth more commonly involved are the molars.…”
Section: Introductionmentioning
confidence: 99%
“…La mayoría de estos métodos incluyen pruebas de hipótesis (pruebas "t" de Student pareadas, análisis de varianzas-ANOVA) o coeficientes de correlación (Pearson y coeficiente de correlación intraclase) (18,22). Otros métodos incluyen análisis de regresión y el coeficiente de variación (23,24). Es de notar que entre los métodos menos considerados está la técnica propuesta por Bland & Altman (límites de acuerdo) y la descrita por Lin (coeficiente de correlación y concordancia de Lin)(25).…”
Section: Discussionunclassified
“…Other studies have demonstrated that the inversion filter did not increase the efficacy in the measurement of bone loss. 7,8 In conclusion, expert and non-expert examiners had a low frequency of use of digital tools during radiographic interpretation. The most preferred tool was sharpness, but this did not improve the diagnostic accuracy.…”
mentioning
confidence: 85%
“…2 In oral pathology, digital manipulation has some influence on radiographic diagnosis, such as contrast adjustments, 3,4 sharpness, smoothness and embossing for caries diagnosis, 5 use of noise filters for detection of vertical root fractures 6 and use of the inversion tool for bone loss measurements in periodontal disease. 7,8 However, digital image manipulation can increase the time taken to interpret the image and this processing may not contribute to an increase in the percentage of correct diagnoses. 2 The great challenge is to know which tools are useful and applicable to each diagnostic task in order to discard superfluous signs and stress useful signs in the images.…”
Section: Introductionmentioning
confidence: 99%